On Top of the Volcano: Missionary Politics in the Twenty-first Century - Zúquete, José Pedro (2016)
This article on comparative politics examines and develops the concept of missionary politics as a contemporary example of the sacralization of politics. Resorting to recent cases in Europe and South America, in this interdisciplinary study the author demonstrates how missionary politics is a form of political religion led by charismatic leaders geared towards a mission of salvation, bringing together followers through political liturgy. The article concludes with a discussion on the consequences of this missionary form of conducting politics for the study of religion, populism, nationalism and democracy.